2022
DOI: 10.3389/fmicb.2022.972928
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation along an altitudinal gradient in the Phytophthora infestans effector gene Pi02860

Abstract: Effector genes, together with climatic and other environmental factors, play multifaceted roles in the development of plant diseases. Understanding the role of environmental factors, particularly climate conditions affecting the evolution of effector genes, is important for predicting the long-term value of the genes in controlling agricultural diseases. Here, we collected Phytophthora infestans populations from five locations along a mountainous hill in China and sequenced the effector gene Pi02860 from &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
2
1
Order By: Relevance
“…This type of gene flow has also been documented in other Phytophthora species (Jung et al., 2017 ). However, this interpretation contradicts our recent observations of genetic variation in an effector gene and UV adaptation of the pathogen, showing a clear pattern of altitudinal distribution (Wang et al., 2021 ; Yang et al., 2022 ). On the other hand, the observed pattern of altitudinal distribution in oospore production may be generated by the interaction between UV and thermal adaptation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This type of gene flow has also been documented in other Phytophthora species (Jung et al., 2017 ). However, this interpretation contradicts our recent observations of genetic variation in an effector gene and UV adaptation of the pathogen, showing a clear pattern of altitudinal distribution (Wang et al., 2021 ; Yang et al., 2022 ). On the other hand, the observed pattern of altitudinal distribution in oospore production may be generated by the interaction between UV and thermal adaptation.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the higher regions receive primary inoculum from lowlands each year. This upwards gene flow of the pathogen is common in Yunnan (Yang et al., 2022 ) due to its year‐round potato production model. This type of gene flow has also been documented in other Phytophthora species (Jung et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, to illustrate this pathogen’s high evolutive ability, Shen et al [ 181 ] analysed the sequence of only one effector (Avr1) of 111 Chinese P. infestans isolates, during a short period (2010–2011), and found that nearly 80% of the isolates have undergone a point mutation. In another study, Yang et al [ 182 ] found that the effector gene Pi02860 has undergone moderate genetic alteration, mainly by point mutation, but resulted in a modification in pathogen fitness. As mentioned above, P. infestans harbours more than 500 RxRL effectors, and this is only one type of effector.…”
Section: Genetic Methodologies For Breeding Resistance To P...mentioning
confidence: 99%